Resources Orchestration to Realizing Global Competitive Universities - Yusuf Amrozi; Wanda Alifiyah Pramesti; Cholifatur Rozzika; Nasihatul Latifah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
Resource orchestration can be an important pioneer in creating competitive advantage in organizations, including world-class universities. There are two dimensions to resource orchestration, namely resource management and asset orchestration. This study aims to look at the implementation and contribution of resource orchestration in the environment of state Islamic religious universities in Indonesia in realizing globally competitive universities. The research method used is descriptive-qualitative, with data collected from interviews, observations, and analysis of related documents at six state Islamic universities. The results showed that the leadership ability of the leaders of state Islamic universities is very decisive in orchestrating resources to encourage the performance of higher education towards globally competitive universities.